2012
DOI: 10.7730/jscm.2012.24.4.100
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Soeumin with Peripheral T-cell Lymphoma who Showed Symptomatic Improvement including Fever, Myalgia, Performance Status, and Headache after Treated with Osuyubujaijung-tang and Geopoong-san

Abstract: ObjectivesThe aim of this study was to report the improvement of fever, myalgia, performance status, and headache after treatment with Osuyubujaijung-tang and Geopoong-san in a Soeumin with Peripheral T-cell lymphoma. MethodsWe retrospectively reviewed the medical records, medical laboratory and image scans of 80-year-old male patient diagnosed as peripheral T-cell lymphoma. He couldn't conduct any conventional chemotherapy due to poor performance status, ECOG 4. ResultsThe symptoms of myalgia, poor performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Choi et al . () showed that Osuyubujaijung‐tang improved the symptoms of myalgia, poor performance status, neck pain, and fever in Soeumin with peripheral T‐cell lymphoma. In a previous study, we found that H9 inhibited proliferation and induced apoptosis in A549 human non‐small‐cell lung cancer cells (Kwon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al . () showed that Osuyubujaijung‐tang improved the symptoms of myalgia, poor performance status, neck pain, and fever in Soeumin with peripheral T‐cell lymphoma. In a previous study, we found that H9 inhibited proliferation and induced apoptosis in A549 human non‐small‐cell lung cancer cells (Kwon et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on combinations of trastuzumab with Oriental medicines have reported synergistic efficacy as well as reduced cancer recurrence, drug resistance and side effects [9,15,[22][23][24][25]. H9 extract (H9) is a formula of nine medicinal herbs derived from a traditional Korean prescription of Osuyubujaijung-tang, which possesses antioxidant and cytoprotective effects and ameliorates the symptoms of peripheral T-cell lymphoma [20,26,27]. The nine Oriental medicinal herbs exhibiting anti-cancer activities compose of H9 as follows: Panax ginseng C. A. Mey.…”
Section: Introductionmentioning
confidence: 99%
“…吳茱萸附子理中湯은 소음인이 腹痛, 泄瀉, 口乾, 身體痛, 心煩躁를 넘어서 手足厥冷이나 전신까지 넓은 냉감이 나타나는 증상에 쓰는 처방이다. 吳茱 萸附子理中湯에 대한 기존 증례로는 저혈압 및 사 지궐랭(四肢厥冷)을 동반한 고령의 극심한 식욕부 진(食慾不振) 환자 치험 1례 6 , 오수유부자이중탕 (吳茱萸附子理中湯) 및 거풍산(祛風散)으로 발열, 통증, 전신 활동도, 두통 호전을 보인 소음인 말초 성 T세포 림프종 환자 1례 7…”
unclassified